Interaction of Bacterial Endotoxin and Liquoid with Blood Platelets: Aggregation and Decrease in the Electrokinetic Charge - Gröttum, K. A; Hjort, P. F; Jeremic, M (Thrombosis and Haemostasis, 1969)
The effects of Endotoxin and Liquoid on the electrophoretic mobility of human platelets and erythrocytes in vitro and on rabbit platelets and erythrocytes in vivo and in vitro have been investigated.Liquoid reduced the electrophoretic mobility of human platelets to 74% of normal and rabbit platelets to 59% in vitro and to 68% of normal in vivo, while the erythrocytes were unchanged. Liquoid induced massive aggregation of both human and rabbit platelets. In very high concentrations, Liquoid increased the electrophoretic mobility of human platelets and did not induce aggregation.Endotoxin reduced the electrophoretic mobility of rabbit platelets to 83% of normal and aggregated the platelets, but had none of these effects on human platelets.The effects of Endotoxin and Liquoid were inhibited by EDTA, but not by ADPase, suggesting that aggregation was not mediated through ADP.We conclude that Liquoid has the same pattern of effects on the electrokinetic charge of platelets and platelet aggregation as the acid polymeric agents dextran sulphate and heparin. There was good correlation between reduction in the electrokinetic charge of the platelets and platelet aggregation. There were striking similarities between the effects of these agents and Endotoxin.